Controlled release of raloxifene by nanoencapsulation: effect on in vitro antiproliferative activity of human breast cancer cells - Fontana MC (Dove Medical Press, 2014)
Márcia Camponogara Fontana, Aline Beckenkamp, Andréia Buffon, Ruy Carlos Ruver Beck Pharmaceutical Sciences Graduate Program, Faculty of Pharmacy, Federal University of Rio Grande do Sul (UFRGS), Porto Alegre, Rio Grande do Sul, Brazil Abstract: Raloxifene hydrochloride (RH) is considered to be an antiproliferative agent of mammary tissue. The aim of this study was to investigate the effect of the encapsulation of RH in polymeric nanocapsules with anionic or cationic surface on its release profile and antiproliferative activity. They were prepared by interfacial deposition of preformed polymer, followed by wide physicochemical characterization. The in vitro RH release was assessed by the dialysis membrane method and the data analyzed by mathematical modeling. The antiproliferative effect on MCF-7 cell viability was investigated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay as well as by counting viable cells. They had high encapsulation efficiency, low polydispersity, and nanometric mean size. Nanocapsules prepared with Eudragit® RS100 and Eudragit® S100 presented positive and negative zeta potentials, respectively. Drug release studies demonstrated controlled release of RH from anionic nanocapsules, which could be explained due to a stronger interaction of the drug to these nanocapsules and the larger amount of entrapped drug. On the other hand, this control was not observed from cationic nanocapsules due to the larger amount of drug adsorbed onto their surface. MCF-7 cell viability studies and cell counting showed that RH-loaded Eudragit® RS100 nanocapsules promote the best antiproliferative activity after 24 hours of treatment, whereas the best activity was observed for RH-loaded Eudragit® S100 nanocapsules after 72 hours. Furthermore, the combined treatment of these formulations improved the antiproliferative effect during the entire treatment. Keywords: polymeric nanocapsules, physicochemical characterization, drug control release, antiproliferative effect, MCF-7